2020
DOI: 10.1002/ajpa.24001
|View full text |Cite
|
Sign up to set email alerts
|

Subsistence strategy was the main factor driving population differentiation in the bidirectional corridor of the African Sahel

Abstract: Objectives: The Sahel belt is occupied by populations who use two types of subsistence strategy, nomadic pastoralism and sedentary farming, and who belong to three linguistic families, Niger-Congo, Nilo-Saharan, and Afro-Asiatic. Little is known, however, about the origins of these two populations and their mutual genetic relationships. Materials and Methods:We have built a large dataset of mitochondrial DNA sequences and Y chromosomal STR haplotypes of pastoralists and farmers belonging to all three linguisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 57 publications
(66 reference statements)
4
33
1
Order By: Relevance
“…This phenomenon was revealed by both linguistic and ethnographic data (Braukämper, 1994; Manfredi, 2012; Owens, 1994), which indicate an incorporation of not only Fulani linguistic and cultural items but also individuals into the Arabic population. Our last study also revealed that this theory can be supported by genetics (Nováčková et al, 2020). The only slight disagreement between the various versions of Baggarization hypothesis lies in the dating and localization of the Arab‐Fulani contact.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…This phenomenon was revealed by both linguistic and ethnographic data (Braukämper, 1994; Manfredi, 2012; Owens, 1994), which indicate an incorporation of not only Fulani linguistic and cultural items but also individuals into the Arabic population. Our last study also revealed that this theory can be supported by genetics (Nováčková et al, 2020). The only slight disagreement between the various versions of Baggarization hypothesis lies in the dating and localization of the Arab‐Fulani contact.…”
Section: Discussionsupporting
confidence: 59%
“…Low genetic structure of the Sahel/Savannah belt, revealed by uniparental markers, inspired the notion of a bidirectional migration corridor situated between the Sahara and tropical rainforests (Černý et al, 2007; Černý et al, 2009; Černý et al, 2011). Other studies, however, stress the importance of pastoralism as a barrier of gene flow (Bučková, Černý, & Novelletto, 2013; Kleisner et al, 2019; Nováčková et al, 2020; Shriner & Rotimi, 2018). In fact, a high degree of endogamy can be observed among the Fulani pastoralists even today (Hampshire & Smith, 2001), especially in fully nomadic groups such as Wodaade (sing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study is to contribute to our understanding of the evolution of bitter taste perception encoded by the TAS2R16 gene in populations across the still understudied region of the Sahel/Savannah belt, where both linguistic and archeological evidence shows that two modes of subsistence featuring different food production strategies have been coexisting for several millennia (Ehret, 2002(Ehret, , 2014Ozainne et al, 2014). Nowadays, this immense region, which can be geographically divided into western, central (Lake Chad Basin), and eastern parts is inhabited by Niger-Congo, Afro-Asiatic, and Nilo-Saharan populations and it has been shown that subsistence mode significantly contributed to its population structure (Novác ˇková et al, 2020).…”
Section: Introductionmentioning
confidence: 99%